Alternatives to custodial sentences: a Maqasidi approach - Boukerroucha, Halima (UPM Press, 2015)
This article discusses issues related to custodial sentences. It addresses jurists’ arguments against these sentences on the ground of their inconsistency with the aim of criminal justice. The article is more concerned with the Muslim jurists’ position; hence, it focuses on examining the consistency of custodial sentences with maqasid al-Shariah to determine their appropriateness to the enforcement of criminal justice and the safeguard of public interest. It also assesses the consistency of this concept with the philosophy of Islamic criminal law and the viability of its application in light of the concept of crime and punishment. For this purpose, the article defines custodial sentences in contemporary legislations. It then analyses the concept of imprisonment in the Quran and the Sunnah, and the practices of the Companions. It also assesses the impacts of custodial sentences in modern practices with the aim to identify the conditions and parameters for alternatives to these custodial sentences within the framework of maqasid al-Shariah in general, and the maqasid of punishments in particular. The article found that although considered as necessary to establish justice and protect society, custodial sentences are not in line with the Shariah principals and objectives. It also proposes a number of Maqasidi-driven parameters that serve as building blocks for the implementation of alternative custodial sentences.